Application of 3D Digital Image Correlation Technique to Measurement of Wind Blade Properties from Coupon Test and Small-Sized-Blade Frequency Test - Kwangtae Ha; Mingyu Kang; Daeyong Kwon; Sungmok Hwang; Cheol Yoo (Energies, 2024)
As a wind blade is getting larger, its structural behavior becomes more complex and thus the risk of blade structural failure becomes higher. Generally, structural integrity is proved through blade testing with contact measurement devices such as strain gauges. However, contact measurement can only measure the physical quantities from installation points and requires lengthy cables to transmit the electrical signals to a data acquisition system, which can cause signal noise and add unnecessary weight. Recently, noncontact measurement techniques such as digital image correlation (DIC) have been widely used in various industries to process images captured from cameras and generate full-field strains and displacements without any mechanical connections such as cables. In this study, the application of three-dimensional DIC to wind blades was investigated; in addition, the material properties of glass-fiber-reinforced plastics used in blades for the measurement of the first frequency were also studied. Tensile testing was performed using coupons equipped with strain gauges and speckle patterns. In addition, a small blade from a 10 kW wind turbine was utilized to measure the first flapwise frequency using DIC and modal tests; the results showed a 2.1% difference between the two different measurements. This research showed that the DIC technique could be an alternative replacement for the traditional measurement technique upon further validation tests.